Research on the Application of Mirror Moulds for Masks - Ye, Weiwen (Manufacturing Technology Journal, 2023)
Precision mirror mould CNC machining is a technology of great importance in industrial manufacturing. Precision mirror moulds are usually used to produce high-precision, high-quality parts and products, which are widely used in automotive manufacturing, aerospace, electronic equipment and other industries. However, the traditional mould polishing process often fails to meet the manufacturing needs of precision moulds, so the application of CNC machining technology has become an effective way to solve this problem. Through the use of CNC machine tools and computer control systems, etc., the detailed formulation of the process plan, so that precision mirror mould CNC machining can achieve high efficiency, accuracy and stability of the machining process, to improve the quality and productivity of the mirror mould. Therefore, the applied research on CNC machining of precision mirror mould is of great significance and economic value.
Keywords: Mirror mould; Process scheme; Validation comparison; Process parameters; Validation effect